Revisiting Islamic Educational Media: The Prophet’s Pedagogical Model and its Relevance for Modern Education: Menelaah Kembali Media Pendidikan Islam: Model Pedagogis Nabi dan Relevansinya bagi Pendidikan Modern - Amelia, Nina; Wahyuni, Sri; Marliana, Fenia; Haulina, Rika; Maslani (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
The global reality, characterized by numerous transformations across various fields, including education, appears to be inversely proportional to the quality of educational outputs. Paradoxically, the educational process conducted by the Prophet Muhammad, despite its contextual limitations, successfully established an exemplary educational model, culminating in the emergence of the finest generation in Islamic history. Arising from this observation, this research aims to examine the pedagogical practices of the Prophet Muhammad as a foundational framework for modern Islamic education, with a specific focus on the educational media he employed. The study is guided by two primary research questions: first, how do the pedagogical practices of the Prophet serve as a basis for constructing modern education? Second, what is the relationship between the Prophet’s educational model and modern education in fostering spiritual embodiment and meaning-making? These questions are investigated and analyzed using a descriptive-analytical approach based on library research. The findings indicate that the fundamental framework of the Prophet’s pedagogical practice was underpinned by his exemplarity and a worldview that each individual should be balanced. This framework was operationalized through three integrated forms of learning media: textual (through reading, writing, and memorization), demonstrative, and critical thinking. Each of these forms possesses distinct benefits and objectives, yet they function synergistically, reinforcing one another within a holistic system. Consequently, the Prophetic pedagogical practice does not rely solely on the verbal transmission of concepts. It comprehensively incorporates experiential learning, moral exemplarity, a deep understanding of learners, and an emotional approach that simultaneously engages students’ cognitive, affective, and psychomotor domains.